2019
DOI: 10.3390/insects10040092
|View full text |Cite
|
Sign up to set email alerts
|

Telenomus remus, a Candidate Parasitoid for the Biological Control of Spodoptera frugiperda in Africa, is already Present on the Continent

Abstract: The fall armyworm, Spodoptera frugiperda, a moth originating from tropical and subtropical America, has recently become a serious pest of cereals in sub-Saharan Africa. Biological control offers an economically and environmentally safer alternative to synthetic insecticides that are being used for the management of this pest. Consequently, various biological control options are being considered, including the introduction of Telenomus remus, the main egg parasitoid of S. frugiperda in the Americas, where it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
108
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 38 publications
8
108
0
1
Order By: Relevance
“…Some authors studied the parasitoid complex of the pest in Ethiopia, Kenya, Tanzania [18,19] and Senegal [20]. In addition, the platygasterid egg parasitoid Telenomus remus Dixon was recorded in Côte d'Ivoire, Benin and Niger [21] and the biology of the braconid larval parasitoid (Coccygidium luteum Brullé) has recently been studied in Ghana [22]. There are many known natural enemies of S. frugiperda from North, Central and South America that play an important role in the natural suppression of this pest in its area of origin (e.g., [23][24][25][26][27][28]) and could potentially be considered for introduction into Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors studied the parasitoid complex of the pest in Ethiopia, Kenya, Tanzania [18,19] and Senegal [20]. In addition, the platygasterid egg parasitoid Telenomus remus Dixon was recorded in Côte d'Ivoire, Benin and Niger [21] and the biology of the braconid larval parasitoid (Coccygidium luteum Brullé) has recently been studied in Ghana [22]. There are many known natural enemies of S. frugiperda from North, Central and South America that play an important role in the natural suppression of this pest in its area of origin (e.g., [23][24][25][26][27][28]) and could potentially be considered for introduction into Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Although some research reported the resistance of FAW to Bt maize 29,30 , multiple genes or new gene with more or new Bt toxin expressed are still thought to have a good performance for resisting the FAW 29,30 . Biological control, including the, introduction of natural enemies and using companion cropping system 19,21,25,31,32 , is also an effective way to resist the FAW.…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis based on COI sequences generated from this study and those used by Kenis et al (2019) showed that the six specimens collected from the three sites of South China were grouped well within the clade of T. remus specimens collected from Asia, Africa, and the Americas (Figure 2). Twenty-eight, five, and three egg masses of S. frugiperda were collected from Huadu, Panyu, and Gaoming, respectively (Table 1).…”
mentioning
confidence: 80%
“…The fall armyworm, Spodoptera frugiperda (Smith) (Lepidoptera: Noctuidae), which originating from the tropical and sub-tropical of North, Central, and South America, has become a invasive pest of cereals in Africa, India, Myanmar, Thailand, etc, where it has caused serious damage (Kenis et al, 2019). This species was first detected in the southeast province of China, Yunnan, in January, 2019, has quickly spread from the south to the north and has now found in 18 provinces (Jiang et al, 2019;Cui et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation